Monitoring and determination of irrigation demand in Cyprus - Papadavid, George; Kountios, Georgios; Michailidis, Anastasios (My University, 2013)
This technical paper describes and interprets the main results of an original research project, which integrates technological tools for developing a complete system for monitoring and determining irrigation demand on a systematic basis in Cyprus. More specifically, the main contribution of this paper consists in the estimation of evapotranspiration (ET) in Cyprus and furthermore in the undertaking of the required measures for a sustainable irrigation water management in the future. The determination of ET is a very difficult procedure, since it combines various meteorological and field parameters, while quite many different estimation models have been indicated in the literature. In this case study, a wireless sensor network is proposed to act as a monitoring tool for providing measurements of the necessary parameters (meteorological, climatic and other auxiliary data required to be included in the irrigation demand models) while reflectance is being determined directly from the satellite images. Geographic Information Systems (GIS) have been used to create a database for the collected data. Taking in to account the great importance of irrigation water as a principal driver in rural development, as well as the increasing demand for irrigation water, the investigation of ways for irrigation water management is extremely valuable, especially in waterscarce areas.
Keywords: Agricultural extension; Waterware software; Evapotranspiration; Irrigation; Precision agriculture; Remote sensing